Cost-Effectiveness of Patient Mailings to Promote Colorectal Cancer Screening - Sequist, Thomas D. (2010)
BACKGROUND: Programs to promote colorectal cancer screening are common, yet information regarding the cost effectiveness of such efforts is limited. OBJECTIVE: To assess the cost effectiveness of patient mailings to increase rates of colorectal cancer screening. RESEARCH DESIGN: Incremental cost-effectiveness analysis of a randomized, controlled trial. The intervention involved 21,860 patients aged 50 to 80 years across 11 health centers overdue for colorectal cancer screening. Patients were randomized to receive a mailing that included a tailored letter, educational brochure, and fecal-occult-blood test kit at baseline and 6 months follow up. MEASURES: We calculated the incremental cost-effectiveness of these mailings to promote colorectal cancer screening via fecal-occult-blood testing, flexible sigmoidoscopy, or colonoscopy using internal cost estimates of labor and supplies. RESULTS: Colorectal cancer screening rates were higher for patients in the intervention compared to control patients (44% versus 38%, p<0.001). The total cost of the intervention was approximately $5.48 per patient, resulting in a cost-effectiveness ratio of $94 per additional patient screened. This estimate ranged from $69 to $156, based on assumptions of the cost of the intervention components, magnitude of intervention effect, age range and size of the targeted patient population. CONCLUSION: Tailored patient mailings are a cost-effective approach to improve rates of colorectal cancer screening.